2003
DOI: 10.1302/0301-620x.85b8.13638
|View full text |Cite
|
Sign up to set email alerts
|

Compression of the Sciatic Nerve by Wear Debris Following Total Hip Replacement: A Report of Three Cases

Abstract: Pain in the distribution of the sciatic nerve is common in the elderly. In the presence of a long-standing joint replacement, consideration should be given as to whether compression might be due to an extraspinal cause. We present three women, in whom a mass of wear debris from a previous total hip replacement caused compression of the sciatic nerve posterior to the hip. The symptoms were relieved immediately following operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 9 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…Sciatic nerve release has also been performed for complications related to wear debris, hardware loosening, or migration [21][22][23][24]. Crawford reported on three patients with long-standing total hip replacements who developed progressive sciatic neuropathy with radicular pain following compression of the nerve by wear debris.…”
Section: Surgical Decompression and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sciatic nerve release has also been performed for complications related to wear debris, hardware loosening, or migration [21][22][23][24]. Crawford reported on three patients with long-standing total hip replacements who developed progressive sciatic neuropathy with radicular pain following compression of the nerve by wear debris.…”
Section: Surgical Decompression and Resultsmentioning
confidence: 99%
“…A hematoma may develop which may progressively compress the nerve resulting in sciatic neuropathy in the early postoperative period [17,18]. Capsular and muscular scarring, hardware debris, or implant migration can irritate the sciatic nerve and present as a delayed neuropathy months to years after surgery [4,[19][20][21][22][23][24].…”
Section: Etiologymentioning
confidence: 99%
“…In our patient, allergy testing confirmed the presence of both nickel and chromium sensitisation, despite no history of allergic reactions or intolerance to metals. Elves et al showed that in patients with metal-on-metal hip replacements, up to 38% of patients were sensitive to one or more of the metals and in those with non-traumatic loosening, up to 65% were sensitive to the metal ions 11. It is unclear as to whether sensitisation to the metal ions causes soft tissue destruction or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Localised reversible sciatic nerve injury following total hip replacement has been reported in cases related to nerve compression from wear debris,11 subfascial haematoma12 and iatrogenic intraoperative pressure on an anatomical variant of the nerve through piriformis muscle 13. In this article, we present an unusual case of irreversible sciatic nerve palsy secondary to metal debris accumulation following hip resurfacing arthroplasty.…”
Section: Introductionmentioning
confidence: 93%
“…These include direct nerve injury, injury from retractors, and postoperative hematoma [14,15,21,29,57]. Delayed-onset sciatic injury from methylmethacrylate [49], trochanteric wire [48], prosthetic dislocation [57], acetabular reinforcement rings [21,47], and wear debris causing an inflammatory reaction and cystic masses compressing the sciatic nerve [18] have also been reported. A recent report suggests that intraoperative retraction of a piriformis muscle through which sciatic nerve fibers penetrate as an anatomic variant could cause what has before been viewed as idiopathic cases of postoperative sciatic neuropathy [22].…”
Section: Nerve Palsy and Hip Arthroplastymentioning
confidence: 99%